2016
DOI: 10.1111/risa.12737
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Stakeholder Involvement in Coastal Disaster Resilience Planning

Abstract: Coastal hazards including storm surge, sea-level rise, and cyclone winds continue to have devastating effects on infrastructure systems and communities despite costly investments in risk management. Risk management has generally not been sufficiently focused on coastal resilience, with community stakeholders involved in the process of making their coastline, as a system, more resilient to coastal storms. Thus, without stakeholder earlier involvement in coastal resilience planning for their community, they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…For instance, Wedawatta and Ingirige [52] proposed a management system approach in order for SMEs pertaining to the construction industry to effectively cope with EWE damages through a triangulation of vulnerabilities (e.g., size of SMEs, location of projects, firm specialization), coping strategies (general risk management, coping strategy at business level) and coping adaptation (e.g., previous experience with EWEs, financial resources). In a similar vein, Bostick et al [53] suggested a stakeholder-based multicriteria model to assist firms in decision-making concerning their resilience status, which consists of five stages: moderated discussion (e.g., resilience, system domain), stakeholder input, decision-maker input, model, output, and reassessment. Likewise, Shashi et al [54] proposed a conceptual model to classify the current literature in organizational resilience regarding supply chain management.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, Wedawatta and Ingirige [52] proposed a management system approach in order for SMEs pertaining to the construction industry to effectively cope with EWE damages through a triangulation of vulnerabilities (e.g., size of SMEs, location of projects, firm specialization), coping strategies (general risk management, coping strategy at business level) and coping adaptation (e.g., previous experience with EWEs, financial resources). In a similar vein, Bostick et al [53] suggested a stakeholder-based multicriteria model to assist firms in decision-making concerning their resilience status, which consists of five stages: moderated discussion (e.g., resilience, system domain), stakeholder input, decision-maker input, model, output, and reassessment. Likewise, Shashi et al [54] proposed a conceptual model to classify the current literature in organizational resilience regarding supply chain management.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To illustrate the method, we made a conscious decision to explore how the existing policies, regulatory framework and management practices could be adapted to meet the overarching objective of enhancing coastal resilience. Our use of MCA, whilst fundamentally data-driven, also uses the explicit representation of stakeholder perspectives to develop a more nuanced understanding of the options and their likely impact (see also Bostick, et al, 2017). Comparing the results for different stakeholder perspectives over multiple scales -from local management unit to national analysis -adds an important dimension that can support the decision-making process.…”
Section: Discussionmentioning
confidence: 99%
“…Disaster losses can create momentum for community engagement in disaster management. After disasters, stakeholders become more interested in activities that reduce future risk and losses to their community (Bostick et al 2017). Disaster impacts also create a heightened sense of urgency and intensify resource competition which motivate citizens to participate in recovery planning (Wilson 2009).…”
Section: Significance and Opportunities Of Participation In Recovery mentioning
confidence: 99%